Peatland paleohydrology in the southern West Siberian Lowlands: Comparison of multiple testate amoeba transfer functions, sites, and Sphagnum δ13C values. (September 2015) - Willis, Katherine S; Beilman, David; Booth, Robert K; Amesbury, Matt; Holmquist, James; MacDonald, Glen
A 2700-year-old peat core from the southern West Siberian Lowlands was used to reconstruct past water-table depth using testate amoeba analysis and to compare hydrological changes with temperature variations associated with the Medieval Climate Anomaly, 'Little Ice Age', and 20th-century warming. The robustness of water-table results was assessed using comparisons of four separate transfer functions, a testate amoeba reconstruction from an additional site in southern West Siberia, and an independent hydrological proxy of the δ 13 C values of Sphagnum remains from the same core. The paleohydrology results were robust in that (1) all four transfer functions returned similar results, (2) both peatland sites displayed very similar water-table fluctuations despite their distance from each other, and (3) Sphagnum δ 13 C values showed similar overall changes as the testate amoeba–inferred hydrology, but at a coarser temporal resolution. When comparing reconstructed hydrology in southern West Siberia to Northern Hemisphere temperatures, we found that during most of the record warmer time intervals tended to be wet locally and cooler time intervals tended to be dry including during the Medieval Climate Anomaly (~1150–650 cal. BP). This pairing continued until the 'Little Ice Age' (~650–100 cal. BP) when conditions became cool and wet, and recently, conditions have become warm again, but unlike the earlier wet interval, the peatlands have dried. Drier conditions shown by the water-table depth reconstruction suggest that future warming may continue the drying of southern peatland surfaces in the West Siberian Lowlands and may promote peat carbon respiration.